2015
DOI: 10.4081/gh.2015.345
|View full text |Cite
|
Sign up to set email alerts
|

The spatial distribution of Schistosoma mansoni infection in four regions of western Côte d’Ivoire

Abstract: Schistosomiasis poses a considerable public health burden in subSaharan Africa and a sound understanding of the spatial distribution facilitates to better target control interventions. The objectives of this study were i) to assess the prevalence of Schistosoma mansoni among school-aged children in four regions of western Côte d'Ivoire; ii) to determine demographic, climatic and environmental factors that influence the distribution of S. mansoni; and iii) to map and predict the distribution of S. mansoni in no… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2016
2016
2024
2024

Publication Types

Select...
7
1
1

Relationship

4
5

Authors

Journals

citations
Cited by 31 publications
(29 citation statements)
references
References 47 publications
0
27
0
2
Order By: Relevance
“…[33][34][35][36][37] Third, our results confirm that schistosomiasis is a focal disease; indeed, the prevalence of infection at the unit of the school showed considerable variation from one school to another. 29 Focality of S. mansoni is often explained with special occupational or recreational risk behaviors, proximity to open freshwater bodies that serve as habitat for intermediate host snails, and access to, and use of, sanitation facilities. [38][39][40][41][42] In our study, for example, boys showed a higher infection prevalence than girls.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…[33][34][35][36][37] Third, our results confirm that schistosomiasis is a focal disease; indeed, the prevalence of infection at the unit of the school showed considerable variation from one school to another. 29 Focality of S. mansoni is often explained with special occupational or recreational risk behaviors, proximity to open freshwater bodies that serve as habitat for intermediate host snails, and access to, and use of, sanitation facilities. [38][39][40][41][42] In our study, for example, boys showed a higher infection prevalence than girls.…”
Section: Discussionmentioning
confidence: 99%
“…S. mansoni prevalence rates above 24% were mainly observed in Tonkpi region, while schools with prevalence of infection ranging between 10% and 24% were predominantly found in Gomon, Cavally, and Haut-Sassandra. 29 Those 75 villages where the S. mansoni prevalence ranged between 10% and 24% and that fulfilled other inclusion criteria were eligible for the SCORE trial. Villages were randomized into one of three treatment arms.…”
Section: Methodsmentioning
confidence: 99%
“…A relação negativa com a altitude coincide com alguns trabalhos, como exemplo, em recente artigo avaliando a esquistossomose em Costa do Marfim (África), utilizando metodologia de distribuição espacial da parasitose identificou-se uma relação negativa entre a altitude e a ocorrência da esquistossomose, sendo aquela a região mais propicia para tal ocorrência, visto que está situada entre 200 e 300 metros de altitude 19 .…”
Section: Discussionunclassified
“…These predictions can be displayed as smoothed risk maps and serve as a decision support tool for health planning and control (Raso et al, 2005;Simoonga et al, 2009;Woodhall et al, 2013;Assare et al, 2015). However, due to the central role of climate, the spatial distribution of schistosomiasis might change in the future with anticipated climate change (McCreesh and Booth, 2013).…”
Section: Introductionmentioning
confidence: 99%